Co-ordination of relay for Microgrid using Directional overcurrent relay - et. al., Dr.S.Padma, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
During the transition between Grid mode of operation to Islanded mode of operation and Loss of generators in the Microgrid, the fault current levels will change not only the fault current level Change will happen, relay pairs also change. It will results in delay operation of the relay or relay operation failure. So we need an optimal and single protection scheme for protection of Micro grid system against over currents. Micro grid protection is one of the most important challenges due to the above said reasons. So single protection scheme must enhance the system reliability and stability of the system with various level of phase faults fault current like LLL, LL and LLG with various modes of operation in micro grid system. Protection is provided by REF 541 (Feeder management Relay).